An Analytic Model Proposal for Ecological Planning - Omerli Watershed Case - Ozugul, Mehmet Doruk (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2006)
The idea of disscussing natural values within the context of conservation - use balance (in other words sustainability of natural resources), has been taking place in planning agenda particularly starting from the last quarter of the former century. This consciousness, which is based on a practical necessity (solution proposals for the wide range environmental problems), directed planning discipline to a well recognition of the natural sciences and particularly ecology. This new orientation, caused some new research fields, like a planning approach that aims to internalize the natural values and some tools serving this aim, to develop. Today, the approach known as Ecological Planning is a product of the above-mentioned attempts. This article, is presenting the findings of a settlement suitability evaluation, which was developed within the framework of Ecological Planning Approach and carried out with the help of a three stepped analytic model proposal, for Omerli Watershed. These three steps could be summarized as follows; an analytic study to state the natural sensitivities of the study area, determination of factors, factor scores and weights (with the help of Analytic Hierarchy Process) for evaluation and Suitability Analysis. The watershed is disscussed with its relatively virgin structure in 1970' s ( using the data of 1970' s) and the findings of suitability evaluation is compared with today's landuse pattern also interpreting actual environmental problems within their cause and effect relations. In other words, the effects of a development approach which is not considering the before- mentioned consciousness is evaluated.
Keywords: Ecological Planning; Suitability Analysis; Analytic Hierarchy Process; Architecture